THE SCIENTIFIC PROBLEM OF BUILDING SOFTWARE SYSTEMS FOR LOGICAL CONTROL OF TECHNOLOGICAL EQUIPMENT - Yuldoshev , Mirzobek Nurilloyevich (Educational Research in Universal Sciences, 2023)
The article presents an urgent scientific problem important for the national economy, the analysis of its systems, which consists in creating theoretical foundations for the construction of modern logical control systems with a wide range of purposes, with an open modular architecture, flexible and configurable software.